Comparative Seismic Evaluation of Building Codes: A Case Study on Structural Performance and Safety - Jovan Thierry Salim; Indra Djati Sidi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
The evolution of structural design standards, from empirical approaches to modern precision, has significantly impacted seismic evaluation and building safety. Indonesia’s adoption of seismic standards in 2002, aligned with global practices like ASCE, introduced notable shifts in seismic design philosophy. This study offers a novel comparison of the seismic performance of a forty-story office building in Jakarta designed under SNI 1726:2002 versus the updated SNI 1726:2019. The unique focus of this research lies in evaluating how the shift from a uniform risk philosophy to a uniform hazard philosophy, alongside changes in earthquake return periods, affects structural safety and performance criteria. A comprehensive seismic evaluation was conducted using both nonlinear static (pushover) and nonlinear time-history analyses (NLTHA), with performance criteria based on ASCE 41-17’s Life Safety and Collapse Prevention levels. By employing both methods, this study uniquely highlights discrepancies between traditional pushover analysis and the more rigorous NLTHA, a comparison rarely explored in the context of Indonesia’s seismic standards. The results revealed significant disparities between the two methods. While pushover analysis exposes potential beam failure under the Collapse Prevention criteria, the NLTHA results suggest a more resilient behavior, indicating that the structure may perform better under real seismic events. These findings emphasize the limitations of pushover analysis and underscore the importance of more detailed nonlinear time-history analyses in accurately assessing the seismic performance of buildings.